1989
DOI: 10.1111/j.1756-1051.1989.tb02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology and systematica of Araceae

Abstract: The chromosome numbers of 75 species belonging to the family Araceae have been determined. The numbers for 53 species are reported for the first time. One number differs from previous reports (Aglaodorum), and one number is corrected (Phymatarum). Within 15 genera (Gymnostachys, Pothoidium, Alloschemone, Heteropsis, Holochlamys, Anaphyllopsis, Dracontioides, Pseudohydrosme, Montrichardia, Bucephalandra, Taccarum, Asterostigma, Gorgonidium, Spathantheum and Ulearum) the chromosome numbers have not previously be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
2
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 142 publications
7
42
2
2
Order By: Relevance
“…Since NAKAJIMA (1936) did the chromosome study on Colocasia esculenta, abundant cytological data were reported for Colocasia (KURAKUBO 1940;ITO 1942;RAO 1947;DELAY 1951;SHARMA and DAS 1954;MOOKERJEA 1955;PFITZER 1957;FUKUSHIMA et al 1962;YEN and WHEELER 1968;BAI et al 1971;KAWAHARA 1978;KURUVILLA et al 1981;COASTES et al 1988;OKADA and HAMBALI 1989;PETERSEN 1989;SREEKUMARI and MATHEW, 1991a, b;KOKUBUGATA and KONISHI 1999), but cytological data are mainly associated with different populations of C. esculenta for its variation of chromosome numbers. Although most species of Colocasia are distributed in China, and 4 new species, C. heterchroma, C. gaoligongensis, C. gongii and C. lihengiae, were recently described from Yunnan Province, China (LI and WEI 1993;LI and LONG 1999;LONG and LI 2000;LONG and LIU 2001), there was no cytological study on these species up to the present time.…”
Section: Introductionmentioning
confidence: 99%
“…Since NAKAJIMA (1936) did the chromosome study on Colocasia esculenta, abundant cytological data were reported for Colocasia (KURAKUBO 1940;ITO 1942;RAO 1947;DELAY 1951;SHARMA and DAS 1954;MOOKERJEA 1955;PFITZER 1957;FUKUSHIMA et al 1962;YEN and WHEELER 1968;BAI et al 1971;KAWAHARA 1978;KURUVILLA et al 1981;COASTES et al 1988;OKADA and HAMBALI 1989;PETERSEN 1989;SREEKUMARI and MATHEW, 1991a, b;KOKUBUGATA and KONISHI 1999), but cytological data are mainly associated with different populations of C. esculenta for its variation of chromosome numbers. Although most species of Colocasia are distributed in China, and 4 new species, C. heterchroma, C. gaoligongensis, C. gongii and C. lihengiae, were recently described from Yunnan Province, China (LI and WEI 1993;LI and LONG 1999;LONG and LI 2000;LONG and LIU 2001), there was no cytological study on these species up to the present time.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme a tabela 1, verifica-se que os dois pares de cromossomos grandes apresentam comprimentos médios de 6,0 e 5,2 µm, sendo que os demais cromossomos são de tamanho médio a pequeno e têm, em média, cerca de 4,1 a 2,8 µm. Anthurium gaudichaudianum possui, portanto, cromossomos de tamanho similar aos de algumas espécies do gênero, tais como A. warocqueanum T. Moore, que possui dois pares grandes, com aproximadamente 6,0 µm, e os pares médios a pequenos variam de 4,0 a 2,8 µm (Kaneko & Kamemoto 1979 (Petersen 1989).…”
Section: Resultsunclassified
“…Okada & Hotta (1987) e Petersen (1989, 1993, ao revisarem a bibliografia sobre o número cromossômico das espécies da família Araceae, verificaram que os números gaméticos relatados variavam de n = 8 a n = 56 e os somáticos de 2n = 10 a 2n = 168. Estudos evolutivos sobre a família Araceae e, em especial, sobre o gênero Anthurium, postulam que essa espécie possa ser um anfidiploide, com um número cromossômico básico secundário x = 15, o qual foi encontrado na maioria das contagens e que se originou através de hibridações e duplicações, a partir de espécies com números básicos x = 7 e x = 8 , Petersen 1989, Grayum 1990, Cotias-de-Oliveira et al 1999. Já, Bogner & Petersen (2007) propoem os números básicos x = 10, 12, 14 e 15 para o gênero Anthurium, em consequência das espécies diploides, tetraploides e hexaploides encontradas.…”
Section: Introductionunclassified
“…As our new results for P. lacerum associates the species with a quite common diploid number for P. subgenus Philodendron (2n = 32), P. rugosum is currently the only species of the mentioned group with a double-checked diploid number of 2n = 36 (Bogner & Bunting 1983;Petersen 1989). In addition, the number 2n = 36 has been observed almost only in the heliophytes of P. subgenus Meconostigma, which has been indicated as a derivative habit within the group (Calazans et al 2014;Loss-Oliveira et al 2016).…”
Section: Short Communicationmentioning
confidence: 91%